Mechanism of grinding-induced burns and cracks in 20CrMnTi steel gear. Issue 10 (27th July 2019) - Wang, Long; Tang, Xiujian; Wang, Liuying; Yang, Nengjun; Chen, Xiaohu; Li, Ping; Liu, Gu; Liu, Guohao
ABSTRACT: To investigate the characteristics and formation mechanism of grinding-induced burns and cracks in 20CrMnTi steel gear, diverse distribution characteristics including metallographic structure, Microhardness, and residual stress of the gear surface were analyzed. Under the effect of thermal-mechanical coupling, the transformation mode of metallographic structures led to different degrees of grinding burns, showing the unique nature of each affected layer. When subjected to tempering-induced burn, martensite was transformed into troostite or sorbite to thus decrease the microhardness and initial residual compressive stress. When being subjected to quenching-induced burn, the fine-grained white layer formed, and the surface microhardness was enhanced, but the residual compressive stress on the gear surface was transformed into tensile stress, resulting in the generation of grinding-induced cracks. By optimizing the grinding parameters and conducting shot peening strengthening treatment, grinding-induced burns or cracks can be prevented.